MENINGKATKAN KETEPATAN BERHITUNG MELALUI STRATEGI JARI PINTAR DALAM PEMBELAJARAN PENJUMLAHAN DAN PENGURANGAN DENGAN PENDEKATAN NILAI-NILAI ISLAM - Dewi Maria Arifiani; Mia Audina Musyadad; Rendi Atnanto (Prodi PGMI STAI Sabili Bandung, 2026)
Arithmetic accuracy refers to a person’s ability to perform arithmetic operations to obtain correct answers in accordance with proper mathematical procedures and concepts. Arithmetic accuracy reflects students’ ability to understand the basic concepts of addition and subtraction and to apply them correctly without making calculation errors. This study aims to analyze the improvement in the computational accuracy of first-grade students at Alief Islamic Elementary School through the application of the “Smart Fingers” strategy using an Islamic values approach. This study employs a quantitative method with a quasi-experimental design. The research subjects consisted of teachers and first-grade students at Alief Islamic Elementary School, totaling 25 students. Data collection techniques included observation, pretest and posttest assessments, and interviews. The research instruments were validated through content validation by experts (expert judgment) and tested using empirical validation as well as Cronbach’s Alpha reliability. Data analysis was performed by calculating the mean scores of the pretest and posttest, conducting an N-Gain analysis, and performing a paired sample t-test using IBM SPSS Statistics software. This showed an increase in the average pretest score from 7.28 to 9.72 on the posttest with a significance value of 0.001 < 0.05; therefore, H₀ was rejected and H₁ was accepted. The results of the study indicate that the implementation of the “Smart Fingers” strategy is capable of improving students’ arithmetic skills.